2020
DOI: 10.1007/s10834-020-09724-6
|View full text |Cite|
|
Sign up to set email alerts
|

Household Savings Decisions in Israel’s Child Savings Program: The Role of Demographic, Financial, and Intrinsic Factors

Abstract: Israel's Child Development Account (CDA) program, the Savings for Every Child Program (SECP), is universal and automatically enrolls all children under the age of 18, depositing approximately $14 into their accounts every month. Parents can transfer an additional monthly $14 into these long-term savings accounts and can choose an investment vehicle for their children's deposits. The total realized benefits from the SECP depend heavily on parents' choices. This study examines how demographic, financial, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In particular, most of the research that explores savings behaviors focuses on financial capabilities (Sherraden, 2013) and knowledge (Lusardi & Mitchell, 2014), access to savings vehicles (Nam et al, 2013), and broader social and economic factors (e.g., Lunt & Livingstone, 1991). By contrast, a small number of studies have examined broad individual differences, such as personality traits, and their relationship with savings behaviors (Asebedo et al, 2019;Matz et al, 2016;Rosen et al, 2021). For example, Loibl et al (2010) found that psychological dispositionsparticularly future orientationswere associated with savings behaviors among participants in a matched savings program.…”
mentioning
confidence: 99%
“…In particular, most of the research that explores savings behaviors focuses on financial capabilities (Sherraden, 2013) and knowledge (Lusardi & Mitchell, 2014), access to savings vehicles (Nam et al, 2013), and broader social and economic factors (e.g., Lunt & Livingstone, 1991). By contrast, a small number of studies have examined broad individual differences, such as personality traits, and their relationship with savings behaviors (Asebedo et al, 2019;Matz et al, 2016;Rosen et al, 2021). For example, Loibl et al (2010) found that psychological dispositionsparticularly future orientationswere associated with savings behaviors among participants in a matched savings program.…”
mentioning
confidence: 99%